Prerequisites for formation of underground spaces - Kholyavko, Anastasia; Druzhinina, Inna (project baikal, 2021)
The article studies the evolution of underground spaces, from the history of their development in the primitive world to the most striking examples of their present-day realization. Particular attention is paid to the development of underground spaces and the ancient world, as well as the period of the industrial revolution, the modern times, when there was a surge in the development of underground urbanistics. The article touches upon modern trends in the development of underground architecture, which involve multipurpose spatial planning and complex development of the interior of the earth. This article is the first publication of the series devoted to this topic.